The ASSURE study: HIV‐1 suppression is maintained with bone and renal biomarker improvement 48 weeks after ritonavir discontinuation and randomized switch to abacavir/lamivudine + atazanavir1. Issue 2 (14th July 2015) - Wohl, DA; Bhatti, L; Small, CB; Edelstein, H; Zhao, HH; Margolis, DA; DeJesus, E; Weinberg, WG; Ross, LL; Shaefer, MS
Abstract : Objectives: HIV treatment guidelines endorse switching or simplification of antiretroviral therapy in therapy‐experienced patients with suppressed viraemia; ritonavir discontinuation may also enhance tolerability and reduce long‐term adverse events (AEs). This open‐label, multicentre, noninferiority study enrolled HIV‐1‐infected, treatment‐experienced adults with confirmed HIV‐1 RNA ≤ 75 HIV‐1 RNA copies/mL currently receiving tenofovir/emtricitabine + atazanavir/ritonavir (TDF/FTC + ATV/r) for ≥ 6 months with no reported history of virological failure. Methods: Participants were randomized 1:2 to continue current treatment or switch to abacavir/lamivudine + atazanavir (ABC/3TC + ATV). Endpoints included the proportion of participants with HIV‐1 RNA < 50 copies/mL by time to loss of virological response (TLOVR), AEs, fasting lipids, and inflammatory, coagulation, bone and renal biomarkers. Results: After 48 weeks, 76% (152 of 199) of ABC/3TC + ATV‐treated and 79% (77 of 97) of TDF/FTC + ATV/r‐treated participants had HIV‐1 RNA < 50 copies/mL (TLOVR; P = 0.564). Other efficacy analyses yielded similar results. Rates of new grade 2–4 AEs were 45% in both groups, but an excess of hyperbilirubinaemia made the rate of treatment‐emergent grade 3–4 laboratory abnormalities higher with TDF/FTC + ATV/r (36%) compared with ABC/3TC + ATV (19%). Most fasting lipid levels remained stable over time; high‐density lipoprotein (HDL) cholesterol increased modestly in ABC/3TC + ATV‐treated participants. Bone and renal biomarkers improved significantly between baseline and week 48 in participants taking ABC/3TC + ATV and were stable in participants taking TDF/FTC + ATV/r. No significant changes occurred in any inflammatory or coagulation biomarker within or between treatment groups. Conclusions: The ABC/3TC + ATV treatment‐switch group had similar viral suppression rates up to 48 weeks to the TDF/FTC + ATV/r comparator group, with lower rates of moderate‐ to high‐grade hyperbilirubinaemia and improvements in bone and renal biomarkers.